Manajemen Pengembangan Kecerdasan Majemuk Melalui Metode Pemberlajaran Quantum Pada Anak Usia Dini - Ach Syaikhu (STAIFAS-Press, 2018)
Management in developing potential (plural intelligence) Early Childhood (AUD) is very important to do. Called Early Childhood, namely children aged 0-6 years. At an early age is a golden age (Golden Age) where during this period the child's process will experience development in itself, both hysical, intellectual, social emotional and language. An understanding of the importance of early childhood has an impact on current government policies. One of these policies is the Republic of Indonesia Law Number 20 of 2003 concerning the National Education system. Basically, almost every early childhood education institution has applied quantum learning ethods, a teaching method where each teacher will enter the world of students so that students feel comfortable and are not faced with the risk of failure in the learning process.